INNOVATIVE CULTURE DEVELOPMENT OF TEACHERS AND PUPILS AS A PEDAGOGICAL IDEA REALIZATION OF THE AUTHOR SCHOOL ON LINGUISTICS AND SPIRITUALITY - Валентина Антоненко (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2021)
The article presents theoretical and methodological, organizational and pedagogical principles of innovative culture of teachers and pupils as a realization of the pedagogical idea of the author's school of linguistics and spirituality of Zarifa Aliieva Irpin specialized secondary school I-III Grades №12 with foreign languages (school of linguistics) of Kyiv region; The author's school model is seen as a prototype of qualitative changes in education, which depends on a team of professionals who expand the space of educational opportunities for pupils development. The leading idea of the Author's School of Linguistics and Spirituality is the formation of a competitive, socially mobile, innovative, tolerant and spiritual personality. Gradually realizing this goal, the teaching staff made every effort to create a positive image of the educational in-stitution, which determines: the presence of a relevant concept of the school of linguistics; implementation of long-term educational strategy; development of innovative culture of teachers and pupils; favorable moral and psychological climate in the team; availability of proper modern material and technical base; caring highly professional teaching staff; functioning of the school pupils organization «Country Roxolania». The introduction of the pedagogical idea of the author's school of linguistics and spirituality in the context of the development of innovative culture of teachers and pupils is based on current regulations. Personal and professional characteristics of a teacher with a high level of innovation culture (stable interest in technological innovation, motivation for creative activity, self-improvement and self-realization in professional activities, overcoming difficulties in innovation; values of professional self-expression in innovation, psychological attitude to innovation; innovative technologies, understanding the goals of innovation in education, knowledge of modern innovations in the practice of working with pupils)